Effects of cisapride on gall bladder emptying, intestinal transit, and serum deoxycholate: a prospective, randomised, double blind, placebo controlled trial. Issue 6 (1st December 2001) - Veysey, M J; Malcolm, P; Mallet, A I; Jenkins, P J; Besser, G M; Murphy, G M; Dowling, R H
Abstract : BACKGROUND: Octreotide inhibits gall bladder emptying and prolongs intestinal transit. This leads to increases in the proportion of deoxycholic acid in, and cholesterol saturation of, gall bladder bile, factors that contribute to the pathogenesis of octreotide induced gall stones. AIMS: To see if an intestinal prokinetic, cisapride, could overcome these adverse effects of octreotide and if so, be considered as a candidate prophylactic drug for preventing iatrogenic gall bladder stones. METHODS: A randomised, double blind, placebo controlled, crossover design was used to examine the effects of cisapride (10 mg four times daily) on gall bladder emptying, mouth to caecum and large bowel transit times, and the proportions of deoxycholic acid and other bile acids, in fasting serum from: (i) control subjects (n=6), (ii) acromegalic patients not treated with octreotide (n=6), (iii) acromegalics on long term octreotide (n=8), and (iv) patients with constipation (n=8). RESULTS: Cisapride had no prokinetic effect on the gall bladder. In fact, it significantly increased both fasting and postprandial gall bladder volumes. However, it shortened mouth to caecum (from 176 (13) to 113 (11) minutes; p<0.001) and large bowel (from 50 (3.0) to 31 (3.4) h; p<0.001) transit times. It also reduced the proportion of deoxycholic acid in serum from 26 (2.3) to 15 (1.8)% (p<0.001), with a reciprocal increase in the proportion of cholic acid from 40 (3.5) to 51 (3.8)% (p<0.01). There were significant linear relationships between large bowel transit time and the proportions of deoxycholic acid ( r =0.81; p<0.001) and cholic acid ( r =−0.53; p<0.001) in fasting serum. INTERPRETATION/SUMMARY: Cisapride failed to overcome the adverse effects of octreotide on gall bladder emptying but it countered octreotide induced prolongation of small and large bowel transit. Therefore, if changes in intestinal transit contribute to the development of octreotide induced gall bladder stones, enterokinetics such as cisapride may prevent their formation.